1997
DOI: 10.1080/10426509708043553
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Lawesson′s Reagent With Arsenic (Iii) Alkoxides

Abstract: New arsenic (111) derivatives of 4-methoxyphenyldithio-and trithiophosphonic acids were obtained in the reactions of Lawesson's reagent with arsenic (111) alkoxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We have recently developed convenient methods for the synthesis of S-organoarsenic(III) derivatives of tetrathiophosphoric, trithiophosphonic, and dithiophosphonic acids on the basis of the reactions of tetraphosphorus decasulfide and 1,3,2,4-dithiadiphosphetane-2,4-disulfides with alkylthioarsenites [16] and alkyl and phenyl ethers of arsinous acids, O,O-dialkyl(phenyl)arsonites, and triakylarsenites [17]. We have now extended this approach to antimony(III) derivatives having Sb-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently developed convenient methods for the synthesis of S-organoarsenic(III) derivatives of tetrathiophosphoric, trithiophosphonic, and dithiophosphonic acids on the basis of the reactions of tetraphosphorus decasulfide and 1,3,2,4-dithiadiphosphetane-2,4-disulfides with alkylthioarsenites [16] and alkyl and phenyl ethers of arsinous acids, O,O-dialkyl(phenyl)arsonites, and triakylarsenites [17]. We have now extended this approach to antimony(III) derivatives having Sb-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently developed facile methods for the synthesis of S-organoarsenic(III) derivatives of dithiophosphonic and trithiophosphonic acids by the action of 1,3,2,4-dithiadiphosphetane-2,4-disulfides [13,14]. We have now found that phenarsazine 2, containing a rather reactive As-S bond, reacts with 2,4-bis(ethylthio)-1,3,2,4-dithiadiphosphetane-2,4-disulfide 3 to yield S-10(5,10-dihydrophenarsazine) SЈ-ethyl SЉ-propyltetrathiophosphate 4 (Reaction 2).…”
Section: Resultsmentioning
confidence: 99%